Determinants of Innovative Leadership, Competence, and Motivation through Job Satisfaction to Improve School Performance in Tangerang - Heru Nugroho; Slamet Riyadi; Setyani Dwi Lestari; Agus Kusnawan; Heni Iswati (Komunitas Dosen Indonesia, 2025)
This study aims to assess the impact of innovative leadership styles, as well as competence and motivation, on job satisfaction, and how these factors can enhance school performance in Tangerang. The study also focuses on highlighting the role of job satisfaction as a mediating variable, which is expected to strengthen the relationship between these factors and school performance. A quantitative approach using Structural Equation Modeling (SEM) was employed in this research. The results indicate that innovative leadership, individual competence, and motivation have a significant positive impact on job satisfaction and institutional performance. Additionally, job satisfaction acts as a mediator in the relationship between these three factors and school performance, suggesting that job satisfaction plays a crucial role in driving overall school performance improvements. The findings provide valuable insights for education leaders to focus on the development of innovative leadership, the enhancement of competence, and motivation. By strengthening these three elements, schools can create a more productive and collaborative work environment.